Relasi antara Mata Pelajaran Aqidah-Akhlak pada Tradisi Berandep di Dusun Sungai Jambu Kabupaten Kayong Utara - Dewi Nur Hayati; Wahab Wahab (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2019)
The culture of the Malays community of Sungai Jambu Hamlet has local wisdom in the tradition of holding the fields which are carried out once a year in cooperation when planting (rice paddy) and harvesting rice (rice cutting) to make work easier to complete quickly. Berandep is held in the morning starting from 6:30 to 10:30 WIB. In the implementation of holding, 4-6 people are formed and carried out in turns. If one of them gets a turn to plant and harvest rice the equipment that must be prepared is a penugal (a tool to make a hole to grow rice), a wood-based planter and a razor blade attached to a wood that is slightly made a hole so that the razor sticks easily to make it easier to plant ( harvest rice), and the last to bring food and drinks to the perpetrator with a grip. This is done to help the perpetrator to have a difficult time when holding or planting and harvesting rice. In this study, researchers used a qualitative approach with ethnographic methods. Based on the research of the tradition above, that from the implementation of the tradition there is a behavior that leads to cooperation and helps others, in the sense of the subject of continuous ethics of the tradition of standing. The implementation of the tradition of berandep is related to the subjects of Aqeedah and Morals as outlined in the material of cooperation, help and good morals in neighboring and social life.